Outcome Based Medical Curriculum: Features, Standards and Challenges (Bangladesh Journal of Medical Education, 2019)
Outcome based education has become vital in Medical curriculum worldwide. It's practiced successfully in many countries. After evidencing the practice worldwide, Eastern University, Sri Lanka (EUSL) developed its curriculum to outcome based. Identifying educational programme outcome is crucial process in outcome based educational practice. The educational outcomes of MBBS programme of EUSL have been matched with international standards. The graduate profile reflects the attributes of graduates, which is physician's potentials at the end of the course. Constructive alignment of curriculum is exhibited in accordance with the Sri Lanka Medical Council (SLMC) guidelines, MBBS programme outcome, the organization of learning contents, teaching learning experiences to achieve the intended learning outcomes and assessments for learning. Assessments for learning (formative assessments) are conducted at the end of the modules and feedbacks are expected to be given to drive the learning. Educational outcomes involve several competencies such as Knowledge, Skills and Attitude. There are several assessment methods have been followed to assess various attributes in EUSL. Teacher takes part in facilitating learning or mentoring students. Assessing the team work skills, critical thinking, problem solving are also the salient features as this outcome based medical curriculum has been implemented to foresee the graduates treating patients in a holistic manner.Bangladesh Journal of Medical Education Vol.10(1) 2019: 34-38